2011
DOI: 10.1038/onc.2011.367
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mediated upregulation of integrin-linked kinase promotes Src-induced tumor progression

Abstract: The tyrosine kinase c-Src is upregulated in various human cancers; however, the molecular mechanisms underlying c-Src-mediated tumor progression remain unclear. Here we show that downregulation of microRNA (miR)-542-3p is tightly associated with tumor progression via c-Src-related oncogenic pathways. In c-Src-transformed fibroblasts and human cancer cells that overexpress c-Src, miR-542-3p is substantially downregulated, and the ectopic expression of miR-542-3p suppresses tumor growth. We identified the integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 43 publications
3
57
0
1
Order By: Relevance
“…Consistent with our results, miR-542-3p has been reported to be down-regulated in colon cancer cell lines and to inhibit colon cancer cell proliferation and invasion via targeting ILK (44). Moreover, overexpression of miR-542-3p induces G 1 and G 2 /M arrest in multiple cancer cell lines, including lung cancer, breast cancer, and cervical cancer (24).…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with our results, miR-542-3p has been reported to be down-regulated in colon cancer cell lines and to inhibit colon cancer cell proliferation and invasion via targeting ILK (44). Moreover, overexpression of miR-542-3p induces G 1 and G 2 /M arrest in multiple cancer cell lines, including lung cancer, breast cancer, and cervical cancer (24).…”
Section: Discussionsupporting
confidence: 78%
“…In vitro studies showed that addition of pre-miR-340 or pre-miR-542-3p led to inhibition of cell growth of colon cancer cells, suggesting these miRNAs to be anti-oncomirs, as has been reported in other cancer types: miR-340 in breast cancer (24) and colorectal (43), and miR-542-3p in colon (27) and lung cancer (26). Furthermore, pre-miR-340 and pre-miR-542-3p suppressed the target genes: c-Met (24) and MITF (25) for miR-340, and Survivin (26) for miR-542-3p.…”
Section: Discussionmentioning
confidence: 82%
“…Five miRNAs were decreased and the other five were increased in BM4 cells from the patients with colorectal cancer with liver metastasis compared with in those without metastasis. Table 1 presents information about each miRNA, including the target molecule and whether it is an anti-oncomir or oncomir according to the available literature (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). All data from the miRNA array are shown in Supplementary microarray results.…”
Section: Distinct Mirna Profiles In Bm4 Cells Between Liver Metastasimentioning
confidence: 99%
“…140 Furthermore, Src downregulates the expression of oncomirs, including miR-99a and miR-542-3p, to promote tumor progression. 143,144 Further elucidation of miRNA pathways should elucidate their clinical relevance and use as biomarkers and potential chemotherapeutic targets.…”
Section: Src Contact Normalization and Mirna Expressionmentioning
confidence: 99%